Non-surgical therapy for the treatment of chronic low back pain in patients with Modic changes: A systematic review of the literature. Issue 7 (July 2022) - Mu, Xiaoping; Peng, Wei; Ou, Yufu; Li, Peifeng; Li, Zhuhai; Wei, Jianxun
Abstract: Background: In absence of uniform therapeutic recommendations, knowledge of the available treatment options for Modic changes (MCs) patients and their safety and effectiveness would be crucial and significant for clinicians and such patients. Objectives: The aim of this study was to provide a systematic review of available studies on non-surgical treatments of MCs. Methods: We performed a systematic review of multiple electronic databases including PubMed, Web of Science, Embase, Cochrane Library, and China National Knowledge Infrastructure for the period until 31st August 2021 to search for studies on non-surgical treatments for MCs in accordance with the guidance of the Cochrane Handbook. Potential studies were screened by their titles and abstracts. The methodological quality of the included studies was independently evaluated by two authors. Final recommendations for the included interventions were developed based on grades of recommendations. The narrative format was adopted to synthesize the findings of the present work. Results: Fifth studies involving a total of 1147 patients were identified for this systematic review. The results of this review demonstrated that spinal manipulation has been suggested as an alternative option for patients with MCs. However, there was insufficient evidence to support that patients with MCs can benefit from the medication and wearing the rigid lumbar brace. Moreover, the rationale and safety for the use of antibiotics in such patients remain highly controversial. Low evidence revealed that exercise therapy might decrease pain intensity only for special subgroups of MCs patients. Conclusions: There is not yet enough evidence to suggest that non-surgical treatments are useful for patients with MCs. Further high-quality, multicenter trials are required to validate the effectiveness of these non-surgical treatments. Abstract : Modic changes, Endplate signal changes, Non-surgical treatments, Systematic review.